Ahimsa Sebagai Kewarganegaraan Kontestatif: Institusionalisasi dan Protes di Asia Selatan - Guntur Ari Wibowo (Jurnal Pengetahuan Sosial dan Sejarah, 2026)
This article examines how Ahimsa was institutionalized as a discourse of nonviolent citizenship in India and how this repertoire resonates in recent South Asian protest movements. Using qualitative document analysis and directed content analysis, the study analyzes Gandhian interpretations of Ahimsa and Satyagraha, Indian education policy documents, curriculum frameworks, and recent scholarly studies on civic resistance. The analysis traces three linked processes: moral translation, institutional transmission, and civic enactment. The findings show that Gandhi recast Ahimsa from a religious ethic into an active political repertoire through Satyagraha. Postcolonial institutions, especially education policy, then preserved Ahimsa as a normative language of citizenship. Recent protests in India, especially the farmers' movement and Shaheen Bagh, continued to use nonviolent repertoires while adapting them to gendered leadership, constitutional claim-making, and digital circulation. Comparative evidence from Bangladesh and Nepal further shows that youth-led civic resistance now relies heavily on networked communication, even when its moral language is not explicitly Gandhian. The article concludes that Ahimsa now operates less as a fixed personal trait than as a contested public language of nonviolent citizenship, strongest institutionally in India and echoed selectively elsewhere in South Asia.